Effects of preoperative cisapride on postoperative aspiration pneumonia in dogs with laryngeal paralysis. (1st November 2018) - Ogden, J.; Ovbey, D.; Saile, K.
Abstract : Objectives: Retrospective evaluation of a preoperative prokinetic protocol using a constant‐rate infusion of a serotonin 5‐HT4 receptor agonist, cisapride, and its association with frequency of postoperative aspiration pneumonia in dogs undergoing unilateral arytenoid lateralisation as compared to a historical population at the same institution. Materials and Methods: Medical records of dogs undergoing unilateral arytenoid lateralisation for laryngeal paralysis were reviewed for historical findings, imaging findings, anaesthesia and surgery durations, perioperative medications and if surgery was performed as an emergency. Aspiration pneumonia events in the first 72 hours after surgery were recorded. The study group received a preoperative cisapride constant‐rate infusion; historical 'controls' did not receive the cisapride protocol. Results: One of 50 dogs in the cisapride group and six of 52 dogs in the historical group developed aspiration pneumonia within the immediate postoperative period. The cisapride protocol was largely well tolerated. A markedly lower rate of aspiration pneumonia in patients administered butorphanol with acepromazine preoperatively and buprenorphine postoperatively was noted, but the overall low frequency of aspiration pneumonia and variation in case management protocols precluded definitive conclusions with respect to optimal perioperative drug choices. Clinical Significance: Laryngeal paralysis is commonly treated by unilateral arytenoid lateralisation, and aspiration pneumonia is one of the most serious potential complications of this procedure. This study suggests that further investigation of a cisapride constant‐rate infusion to prevent this complication is warranted.